Pembuatan Perencanaan Pemenuhan Pesanan Produk Brand di PT X - Christofer Soegito; Benedictus Rahardjo (Jurnal Titra, 2019)
PT. X is a company that manufactures motorcycle parts, one of its’ product is motor chain. PT. X sells two kinds of products, namely OEM and aftermarket. OEM products are manufactured products, while aftermarket products are brand products. Some examples of aftermarket products are chains, v-belts, air filters, and chain kits. Aftermarket products are divided into two, namely RM products and brands. Aftermarket products are manufactured by using “make to stock” principle. This kind of production process that implement these principles should have good forecasting and good order fulfillment planning. All this time, PT. X does not have any plan related to two factors which have been mentioned above, thus, PT. X often experiences stock buildup and backorder. These problems can be overcome by making production planning in the form of Master Production Schedule (MPS), where the MPS will display the amount of production that will be carried out each month. The amount of the production can be obtained by forecasting. By using the MPS, PT. X is expected to be able to reduce the accumulation of stock that occurs and the backorder. The decrease in the number of backorder will have an impact on customer satisfaction of PT. X.